THE INFLUENCE OF LEARDERSHIP ETHICS, ORGANIZATIONAL CULTURE, AND INTELLECTUAL CAPITAL ON EMPLOYEES ABILITY TO INNOVATE: LITERATURE REVIEW - Utami, Lia Nur; Hadi, Syamsul; Septyarini , Epsilandri (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
This article aims to understand a literature review of the influence of leadership ethics, organizational culture, and intellectual capital on employees ability to innovate. This research used a systematic literature review (SLR) method with 30 journals and articles obtained form google scholar, and the national library using the keywords “leadership ethics, organizational culture, intellectual capital and innovation ability” which were then reviewed by the result of previous research. Which shows that leadership ethics, organizational culture, intellectual capital and the ability to innovate role for the company. Several results of the literature review can provide an in-depth understanding of employees ability to innovate, and these findings can be used as a reference for future researches.